1988
DOI: 10.1111/j.1600-0676.1988.tb00985.x
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection of epidermal growth factor receptor (EGF‐R), epidermal growth factor (EGF) and ras p21 in cholangiocarcinoma by an immunocytochemical method

Abstract: ABSTRACT— Expression of the epidermal growth factor (EGF), EGF receptor (EGFR) and ras oncogene product p21 was simultaneously examined in 37 cases with intrahepatic cholangiocarcinoma (CC) by means of an immunocytochemical method. While normal livers were all negative for any of the antigens at the concentration of the antibodies used, EGF‐R was positive in 12 (32.4%) CCs, EGF in 22 (59.5%), and ras p21 in 33 (89.2%). The positive incidence of the three antigens was not different among the histologic subtypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 20 publications
1
19
0
1
Order By: Relevance
“…It is known that a subset of ICC exhibit overexpression of the EGF and HER-2 receptor [34] . Indeed, in our study group 21.3% (13/61) of ICC showed strong EGFR overexpression, which was confirmed by others [35] . Due to the relatively large subset of ICC with EGF or HER-2 expression activation of these ligands might be relevant for the progression of ICC.…”
Section: Activation By Growth Factorssupporting
confidence: 77%
“…It is known that a subset of ICC exhibit overexpression of the EGF and HER-2 receptor [34] . Indeed, in our study group 21.3% (13/61) of ICC showed strong EGFR overexpression, which was confirmed by others [35] . Due to the relatively large subset of ICC with EGF or HER-2 expression activation of these ligands might be relevant for the progression of ICC.…”
Section: Activation By Growth Factorssupporting
confidence: 77%
“…The epidermal growth factor receptor (EGFR), a transmembrane tyrosine kinase receptor, is widely expressed in various solid tumors, and its expression level is correlated with malignancy, metastatic phenotype and poor prognosis [1][2][3]. For these reasons, EGFR is considered an important target for cancer therapeutic reagents, including therapeutic antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated overexpression of EGFR and VEGFR, or mutations of their signaling pathways in biliary tract cancer [27]. Nonomura et al [28] reported overexpression rates by 32.4% of EGFR, by 59.5% of EGF, and by 89.2% of ras p21 in 37 intrahepatic cholangiocarcinomas, with all the rates being statistically significantly different as compared with those in normal tissues. Recently, Yoshikawa et al [29] demonstrated EGFR, VEGF and human epidermal growth factor receptor (HER) 2 overexpression in 27.4, 53.8 and 0.9% cases of intrahepatic cholangiocarcinoma, and in 19.2, 59.2 and 8.5% of cases of extrahepatic cholangiocarcinoma, respectively.…”
Section: Preclinical Studies Of the Molecular Biology Of Biliary Tracmentioning
confidence: 99%